Sorção de CO2 com líquido iônico aditivado com extensores de área superficial - Souza, André Luiz Anton de (2017)
In recent years the scientific community has a growing interest in studying environmentally friendly agents sorption of carbon dioxide to be used in substitution of chemical solvents based on amines. Among the technologies studied for this purpose are those which use Ionic liquids that have the advantage of having very low vapor pressures, higher density than water, a low melting point and a desorption low energy; These qualities that make them environmentally friendly solvents, compared with volatile organic solvents. Moreover ionic liquids are chemically and thermally stable and can be used at relatively high temperatures, its physical-chemical properties can be designed by varying the substitutive groups of the cation or the combined ion. These characteristics make ionic liquids potentially important for the development of new processes focused on the mitigation of global warming. Otherwise the ionic liquids have a high viscosity, they are expensive making them economically unfeasible for use in conventional processes with liquid gas absorption columns. On the other side are available in the market the bubble glass that have several applications in the industry, have low cost, high chemical and physical resistance. This work evaluated in isochoric saturation cell, the carbon dioxide solubility in mixed systems with boron silicate bubble glass, with volumetric concentrations of 5% to 50%, in the ionic liquids [Bmim][BF4] and [mBmim] [NTf2] as well as with pure ionic liquids. Data are reported at 27 Bar pressure and at temperatures 303, 313, and 323 K. Mixed systems with 50% concentration of bubble glass showed the best results of sorption and cost for both ionic liquids.